Acrylic adhesive composition, acrylic adhesive, and surface protective film

By controlling the glass transition temperature and composition design of acrylic adhesives, the problem of achieving both low-speed and high-speed peelability in existing acrylic adhesives has been solved, achieving good low-speed and high-speed peelability and meeting the diverse needs of surface protective films.

CN120958097APending Publication Date: 2025-11-14NITTO DENKO CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202480026086.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-20
Filing Date
2024-03-05
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

Existing acrylic adhesive compositions struggle to simultaneously achieve good low-speed and high-speed peelability, failing to meet the peeling requirements of surface protective films in different processes.

Method used

By controlling the glass transition temperature (Tg) of the acrylic adhesive within the range of -25°C to 15°C, and using a water-dispersible adhesive composition containing an acrylic polymer emulsion and a crosslinking agent, a suitable adhesive layer is formed using a specific octanol/water partition coefficient and a reactive emulsifier.

Benefits of technology

The acrylic adhesive composition exhibits good peelability under both low and high speed conditions, meeting the peeling requirements of the surface protective film in different processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention provides an acrylic pressure-sensitive adhesive composition capable of forming an acrylic pressure-sensitive adhesive suitable for a surface protective film capable of exhibiting both good low-speed peelability and good high-speed peelability. An acrylic pressure-sensitive adhesive suitable for a surface protective film which is formed from such an acrylic pressure-sensitive adhesive composition and which can exhibit both good low-speed peelability and good high-speed peelability; and a surface protective film having an adhesive layer comprising such an acrylic adhesive and capable of exhibiting both good low-speed peelability and good high-speed peelability. The acrylic pressure-sensitive adhesive composition according to an embodiment of the present invention is an acrylic pressure-sensitive adhesive composition containing an acrylic polymer, wherein the measured glass transition temperature (Tg) of an acrylic pressure-sensitive adhesive formed from the acrylic pressure-sensitive adhesive composition is-25 DEG C to 15 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to acrylic adhesive compositions, acrylic adhesives, and surface protective films. Typically, this invention relates to acrylic adhesive compositions, acrylic adhesives formed from the acrylic adhesive compositions, and surface protective films having an adhesive layer composed of the acrylic adhesives. Background Technology

[0002] Surface protective films are provided on the surfaces of optical devices such as displays and imaging devices, electronic devices, and the films and glass materials that are components of these devices, for purposes such as surface protection and imparting impact resistance. As a representative example of surface protective films, there are re-peelable surface protective films, which are temporarily applied in the state before use, such as during device assembly, processing, and transportation, and are then peeled off before the device is used.

[0003] The re-peelable surface protective film has an adhesive layer made of a re-peelable adhesive on the main surface of the substrate, and is adhered to the surface of the object to be protected via the adhesive layer.

[0004] Previously, as re-peeling adhesives, acrylic adhesives formed from acrylic adhesive compositions containing acrylic polymers, such as solvent-based acrylic adhesives and water-dispersible acrylic adhesives, were representative examples. Furthermore, since solvent-based acrylic adhesives contain organic solvents with high environmental impact, a transition to water-dispersible acrylic adhesives that do not use organic solvents has been studied against the backdrop of the recent global trend towards reducing environmental impact.

[0005] As an adhesive composition capable of forming a re-peelable water-based acrylic adhesive suitable for surface protective films, a re-peelable water-based adhesive composition is reported, characterized in that it is formed by containing an emulsion [A] and a crosslinking agent [B], wherein the emulsion [A] is obtained by emulsion polymerization of a monomer mixture containing 50 to 99.8% by weight of an alkyl (meth)acrylate (a1) containing 4 to 12 carbon atoms, 0.1 to 20% by weight of a carboxyl-containing unsaturated monomer (a2), 0.1 to 20% by weight of a multifunctional unsaturated monomer (a3), and 0 to 49.8% by weight of other unsaturated monomers (a4) in the presence of an anionic reactive emulsifier (Patent Document 1).

[0006] A surface protection sheet is reported, which is formed from an acrylic-based aqueous emulsion adhesive composition in which the internal structure of polymer emulsion particles is set as cross-linked. The surface protection sheet is obtained by coating one side of a soft polyvinyl chloride sheet with an aqueous emulsion pressure-sensitive adhesive composition and drying it. The pressure-sensitive adhesive composition is obtained by emulsion polymerization of a monomer mixture consisting of a main monomer with alkyl (meth)acrylate having 1 to 8 carbon atoms as the main component and a polyfunctional monomer having two or more olefinic double bonds in the molecule at a ratio of 0.1 to 10 parts by weight relative to 100 parts by weight of the main monomer (Patent Document 2).

[0007] Recently, with the diversification of components for which surface protective films are applied and the increased production efficiency of production processes using surface protective films, the re-peelability of surface protective films has become increasingly important. This demands not only good low-speed peeling (e.g., peeling speed = 0.3 m / min) but also good high-speed peeling (e.g., peeling speed = 30 m / min). However, conventional surface protective films, which have an adhesive layer composed of an acrylic adhesive formed from an acrylic adhesive composition, cannot be said to simultaneously exhibit good low-speed peeling and good high-speed peeling properties.

[0008] Existing technical documents

[0009] Patent documents

[0010] Patent Document 1: Japanese Patent Application Publication No. 2004-256789

[0011] Patent Document 2: Japanese Patent Publication No. 61-268782 Summary of the Invention

[0012] The problem that the invention aims to solve

[0013] The problem of this invention is to provide an acrylic adhesive composition capable of forming an acrylic adhesive suitable for simultaneously exhibiting good low-speed peel and good high-speed peel properties. The problem of this invention is also to provide an acrylic adhesive formed from such an acrylic adhesive composition suitable for simultaneously exhibiting good low-speed peel and good high-speed peel properties. The problem of this invention is further to provide a surface protective film having an adhesive layer composed of such an acrylic adhesive that simultaneously exhibits good low-speed peel and good high-speed peel properties.

[0014] Solution for solving the problem

[0015] [1] The acrylic adhesive composition of the present invention is an acrylic adhesive composition containing an acrylic polymer, and the measured glass transition temperature Tg of the acrylic adhesive formed by the acrylic adhesive composition is -25°C to 15°C.

[0016] [2] In the acrylic adhesive composition described in [1] above, the measured glass transition temperature Tg may be -15℃ to 5℃.

[0017] [3] In the acrylic adhesive composition described in [1] or [2] above, the acrylic adhesive composition may also be a water-dispersible acrylic adhesive composition containing an acrylic polymer emulsion (A) and a crosslinking agent (B).

[0018] [4] In the acrylic adhesive composition described in [3] above, the acrylic polymer emulsion (A) may be obtained by emulsion polymerization of a monomer composition containing alkyl (meth)acrylate (component a), a monomer containing a polar group (component b), and a polyfunctional monomer with trifunctionality or above (component c) in the presence of a reactive emulsifier (component d).

[0019] [5] In the acrylic adhesive composition described in [4] above, the alkyl methacrylate (a component) may be two or more components, and the difference between the maximum and minimum values ​​of the octanol / water partition coefficient LogPow shown by the alkyl methacrylate (a component) is 0.5 or more.

[0020] [6] In the acrylic adhesive composition described in [5] above, the difference between the maximum and minimum values ​​of the octanol / water partition coefficient LogPow may be 1.0 or more.

[0021] [7] In any of the acrylic adhesive compositions described in [4] to [6] above, the alkyl methacrylate (a component) may be a combination of methyl methacrylate and alkyl methacrylate having 2 to 8 carbon atoms.

[0022] [8] In any of the acrylic adhesive compositions described in [4] to [7] above, the polar monomer (component b) may be at least one selected from the group consisting of hydroxyl monomers and carboxyl monomers.

[0023] [9] In any of the acrylic adhesive compositions described in any of [4] to [8] above, the reactive emulsifier (component d) may also be an anionic reactive emulsifier.

[0024]

[10] In any of the acrylic adhesive compositions described in any of [3] to [9] above, the crosslinking agent (B) may also be an oil-soluble crosslinking agent.

[0025]

[11] In the acrylic adhesive composition described in

[10] above, the crosslinking agent (B) may also be an oil-soluble epoxy crosslinking agent.

[0026]

[12] The acrylic adhesive of the present invention is formed from any one of the acrylic adhesive compositions described in [1] to

[11] above.

[0027]

[13] The acrylic adhesive of the present invention has an adhesive layer composed of the acrylic adhesive described in

[12] above.

[0028] Invention Effects

[0029] According to the present invention, an acrylic adhesive composition capable of forming an acrylic adhesive suitable for simultaneously exhibiting good low-speed peel strength and good high-speed peel strength is provided. According to the present invention, an acrylic adhesive formed from such an acrylic adhesive composition is also provided, suitable for simultaneously exhibiting good low-speed peel strength and good high-speed peel strength. According to the present invention, a surface protective film having an adhesive layer composed of such an acrylic adhesive, capable of simultaneously exhibiting good low-speed peel strength and good high-speed peel strength, is also provided. Detailed Implementation

[0030] In this specification, where the term "weight" is used, it may be replaced with "mass," which is commonly used as a SI unit for expressing weight.

[0031] In this specification, the expression "(meth)acrylic acid" refers to "acrylic acid and / or methacrylic acid", the expression "(meth)acrylate" refers to "acrylate and / or methacrylate", the expression "(meth)allyl" refers to "allyl and / or methylallyl", and the expression "(meth)acrylaldehyde" refers to "acrylaldehyde and / or methacrolein".

[0032] Acrylic Adhesive Compositions

[0033] The acrylic adhesive composition of the embodiments of the present invention is an acrylic adhesive composition comprising an acrylic polymer.

[0034] The acrylic adhesive compositions of the embodiments of the present invention can be solvent-based acrylic adhesive compositions containing an acrylic polymer as a base polymer, or water-dispersible acrylic adhesive compositions containing an acrylic polymer emulsion (A) and a crosslinking agent (B). From the viewpoint of reducing environmental impact, water-dispersible acrylic adhesive compositions that do not use organic solvents are preferred embodiments of the present invention.

[0035] Regarding the acrylic adhesive composition according to embodiments of the present invention, the measured glass transition temperature (Tg) of the acrylic adhesive formed from this acrylic adhesive composition is typically -25°C to 15°C, preferably -20°C to 10°C, more preferably -15°C to 5°C, further preferably -14°C to 5°C, and particularly preferably -13°C to 5°C. With the measured glass transition temperature (Tg) within the above range, an acrylic adhesive composition capable of forming a surface protective film suitable for simultaneously exhibiting good low-speed peel strength and good high-speed peel strength can be achieved. If the measured glass transition temperature (Tg) deviates from the above range and is too small, the effects of the present invention may not be apparent; for example, the high-speed peel strength may become too large, resulting in poor high-speed peel strength. If the measured glass transition temperature (Tg) deviates from the above range and is too large, the effects of the present invention may not be apparent; for example, the low-speed peel strength may become too small, resulting in poor low-speed peel strength, and the high-speed peel strength may become too small, resulting in poor high-speed peel strength.

[0036] The measured glass transition temperature Tg mentioned above is the measured value of the glass transition temperature of an acrylic adhesive formed from an acrylic adhesive composition. Specifically, the measured glass transition temperature Tg is obtained by measuring the glass transition temperature through dynamic viscoelasticity, as described in the examples below as a measurement method. This involves stacking layers of an acrylic adhesive composed of an acrylic adhesive composition to form a thickness of approximately 1 mm, punching it into a disc shape with a diameter of 8 mm, using it as a sample for measurement.

[0037] In order to develop an acrylic adhesive composition capable of forming an acrylic adhesive that simultaneously exhibits good low-speed peelability and good high-speed peelability, the inventors conducted in-depth research. Focusing on the glass transition temperature (Tg) of the acrylic adhesive, they first studied the calculated Tg based on the Fox formula, which is commonly used for the Tg of acrylic adhesives. However, no correlation was observed between the calculated Tg and the simultaneous manifestation of good low-speed peelability and good high-speed peelability. Therefore, the inventors conducted research using the aforementioned measured Tg, which is not commonly used for the Tg of acrylic adhesives. The results showed that the measured Tg was clearly correlated with the simultaneous manifestation of good low-speed peelability and good high-speed peelability. Further detailed and repeated studies were conducted, thereby completing the present invention.

[0038] A preferred embodiment of the acrylic adhesive composition of the present invention is a water-dispersible acrylic adhesive composition comprising an acrylic polymer emulsion (A) and a crosslinking agent (B).

[0039] Acrylic polymer emulsion (A) is obtained by emulsion polymerization of a monomer composition comprising (meth)acrylate (component a), a monomer containing a polar group (component b), and a polyfunctional monomer with three or more functions (component c), in the presence of a reactive emulsifier (component d). In other words, acrylic polymer emulsion (A) comprises an acrylic polymer obtained by emulsion polymerization of a monomer composition comprising (meth)acrylate (component a), a monomer containing a polar group (component b), and a polyfunctional monomer with three or more functions (component c), in the presence of a reactive emulsifier (component d).

[0040] The difference between the maximum and minimum values ​​of the octanol / water partition coefficient LogPow shown for (meth)acrylate (component a) is preferably 0.5 or more, more preferably 0.8 or more, further preferably 1.0 or more, more preferably 1.2 or more, more preferably 1.4 or more, more preferably 1.6 or more, particularly preferably 1.8 or more, and most preferably 2.0 or more. The upper limit of the difference between the above maximum and minimum values ​​is preferably 6.0 or less, more preferably 5.0 or less, and further preferably 4.0 or less. The octanol / water partition coefficient LogPow, standardized by JIS Z 7260-117:2006, is an indicator that a higher value indicates higher hydrophobicity. If the above octanol / water partition coefficient LogPow is within the above range, the effects of the present invention can be further demonstrated. It should be noted that the premise for calculating the difference between the maximum and minimum values ​​of the octanol / water partition coefficient LogPow shown by (meth)acrylate (component a) is that (meth)acrylate (component a) has two or more components (preferably two to ten components, more preferably two to seven components, further preferably two to five components, and particularly preferably two to three components). This is one of the preferred embodiments of the present invention.

[0041] As an alkyl methacrylate (component a), representative examples include alkyl methacrylates having an alkyl group having 1 to 20 carbon atoms as the alkyl ester moiety. Examples of such alkyl methacrylates (component a) include, for example, methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, isopropyl methacrylate, isobutyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, amyl methacrylate, isoamyl methacrylate, neopentyl methacrylate, hexyl methacrylate, cyclohexyl methacrylate, heptyl methacrylate, 2-ethylhexyl methacrylate, octyl methacrylate, and methacrylate. Isooctyl acrylate, nonyl acrylate, isononyl acrylate, decyl acrylate, isodecyl acrylate, undecyl acrylate, dodecyl acrylate, isotridecyl acrylate, tetradecyl acrylate, isotetradecyl acrylate, pentadecyl acrylate, hexadecyl acrylate, heptadecanyl acrylate, octadecyl acrylate, isooctadecyl acrylate, nonadecanyl acrylate, eicosyl acrylate.

[0042] Alkyl methacrylate (component a) may be a single component or two or more components. As described above, alkyl methacrylate (component a) typically comprises two or more components, preferably two to ten components, more preferably two to seven components, even more preferably two to five components, and particularly preferably two to three components.

[0043] The alkyl group of the alkyl ester portion of (meth)acrylate (component a) is typically an alkyl group having 1 to 20 carbon atoms, as described above, preferably an alkyl group having 1 to 16 carbon atoms, more preferably an alkyl group having 1 to 12 carbon atoms, even more preferably an alkyl group having 1 to 10 carbon atoms, and particularly preferably an alkyl group having 1 to 8 carbon atoms.

[0044] As a preferred embodiment of (meth)acrylate (component a), it is a combination of methyl methacrylate and alkyl (meth)acrylates having alkyl groups having 2 to 8 carbon atoms. Examples include a combination of methyl methacrylate (MMA) and 2-ethylhexyl acrylate (2EHA), a combination of methyl methacrylate (MMA) and n-butyl acrylate (BA), and a combination of methyl methacrylate (MMA) and ethyl acrylate (EA). In this embodiment, from the perspective of further demonstrating the effects of the present invention, the content of alkyl (meth)acrylates having 2 to 8 carbon atoms in the total of methyl methacrylate and alkyl (meth)acrylates having alkyl groups having 2 to 8 carbon atoms is preferably 30% to 99.9% by weight, more preferably 40% to 99% by weight, further preferably 45% to 98% by weight, particularly preferably 50% to 97% by weight, and most preferably 55% to 96% by weight.

[0045] In the above-described combination of methyl methacrylate and alkyl methacrylate having 2 to 8 carbon atoms, a preferred embodiment is the combination of methyl methacrylate (MMA) and 2-ethylhexyl acrylate (2EHA). In this embodiment, from the perspective of further demonstrating the effects of the present invention, the content of 2-ethylhexyl acrylate (2EHA) in the total of methyl methacrylate (MMA) and 2-ethylhexyl acrylate (2EHA) is preferably 30% to 99.9% by weight, more preferably 40% to 95% by weight, further preferably 45% to 90% by weight, even more preferably 45% to 85% by weight, particularly preferably 50% to 80% by weight, and most preferably 55% to 75% by weight.

[0046] As for the alkyl methacrylate (component A), from the perspective of further demonstrating the effects of the present invention, it can be selected such that the glass transition temperature (Tg) of the acrylic polymer obtained from component A falls within a specified range. The glass transition temperature (Tg) of the acrylic polymer composed of component A, as mentioned here, refers to the glass transition temperature (Tg) of the acrylic polymer composed entirely of monomers of component A, calculated using the Fox formula based on the glass transition temperature (Tg) of the homopolymer of each monomer contained in component A and the weight fraction of that monomer (copolymerization ratio on a weight basis).

[0047] As shown below, the Fox formula is a formula relating the glass transition temperature Tg of a copolymer to the glass transition temperature Tgi of a homopolymer obtained by homopolymerizing the monomers constituting the copolymer.

[0048] 1 / Tg = Σ(Wi / Tgi)

[0049] In the Fox formula above, Tg represents the glass transition temperature of the copolymer (in K), Wi represents the weight fraction of monomer i in the copolymer (copolymerization ratio on a weight basis), and Tgi represents the glass transition temperature of the homopolymer of monomer i (in K). The glass transition temperature Tg of the homopolymer is assumed to be a value recorded in publicly available sources.

[0050] The glass transition temperature Tg of the homopolymer can be, for example, the following values.

[0051] Homopolymer of 2-ethylhexyl acrylate (2EHA): -70℃

[0052] Homopolymer of cyclohexyl methacrylate (CHMA): 66℃

[0053] Homopolymer of n-butyl acrylate (BA): -54℃

[0054] Homopolymer of ethyl acrylate (EA): -20℃

[0055] Homopolymer of methyl methacrylate (MMA): 105℃

[0056] For homopolymers other than those exemplified above, the glass transition temperature (Tg) can be the value recorded in the *Polymer Handbook* (3rd edition, John Wiley & Sons, Inc., 1989). If multiple values ​​are recorded in the *Polymer Handbook*, the conventional value shall be used. For monomers not recorded in the *Polymer Handbook*, the value from the monomer manufacturer's product catalog shall be used. For homopolymers of monomers not recorded in the *Polymer Handbook* and for which no monomer manufacturer's product catalog value is provided, the glass transition temperature (Tg) shall be the value obtained using the measurement method described in Japanese Patent Application Publication No. 2007-51271.

[0057] From the perspective of further demonstrating the effects of the present invention, the glass transition temperature Tg of the acrylic polymer obtained from component a, calculated by the Fox formula above, is preferably -100°C to -10°C, more preferably -90°C to -15°C, further preferably -80°C to -20°C, particularly preferably -70°C to -20°C, and most preferably -60°C to -20°C.

[0058] From the perspective of further demonstrating the effects of the present invention, the content of alkyl methacrylate (component a) in the monomer composition comprising alkyl methacrylate (component a), a monomer containing a polar group (component b), and a polyfunctional monomer with trifunctionality or higher (component c) is preferably 50% to 99.9% by weight, more preferably 60% to 99% by weight, even more preferably 70% to 99% by weight, even more preferably 80% to 99% by weight, even more preferably 85% to 99% by weight, even more preferably 90% to 99% by weight, even more preferably 91% to 99% by weight, even more preferably 92% to 99% by weight, even more preferably 93% to 98.5% by weight, and even more preferably 94% to 98% by weight.

[0059] As the monomer containing a polar group (component b), any monomer having a polar group is acceptable, and any suitable monomer can be used without impairing the effects of the present invention. From the perspective of further demonstrating the effects of the present invention, at least one of the monomers containing a polar group (component b) is preferably selected from the group consisting of hydroxyl-containing monomers and carboxyl-containing monomers. It should be noted that the term "hydroxyl" here does not include the OH portion present in a carboxyl group (-COOH).

[0060] The monomer containing a polar group (component b) may be only one type or two or more types. The monomer containing a hydroxyl group may be only one type or two or more types. The monomer containing a carboxyl group may be only one type or two types.

[0061] Examples of hydroxyl-containing monomers include 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 3-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, and 4-hydroxybutyl methacrylate.

[0062] Examples of carboxyl-containing monomers include (meth)acrylic acid, (meth)acrylic acid dimer, crotonic acid, itaconic acid, and maleic acid.

[0063] As a preferred embodiment of the monomer containing a polar group (component b), it is a carboxyl-containing monomer, preferably (meth)acrylic acid, and more preferably acrylic acid (AA).

[0064] From the perspective of further demonstrating the effects of the present invention, the content of the polar monomer (component b) in the monomer composition comprising (meth)acrylate (component a), a polar monomer (component b) and a polyfunctional monomer with trifunctionality or above (component c) is preferably 0.01% to 15% by weight, more preferably 0.1% to 10% by weight, further preferably 0.5% to 6% by weight, and particularly preferably 0.75% to 5% by weight.

[0065] As a multifunctional monomer (component c) with three or more functions, examples include trimethylolpropane tri(meth)acrylate, bis(trimethylolpropane tetra(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, bispentaerythritol hexa(meth)acrylate, bispentaerythritol hexa(meth)acrylate, bispentaerythritol penta(meth)acrylate, tripentaerythritol hexa(meth)acrylate, and tripentaerythritol penta(meth)acrylate.

[0066] From the perspective of further demonstrating the effects of the present invention, the content of the multifunctional monomer (component c) in the monomer composition comprising (meth)acrylate (component a), a monomer containing a polar group (component b), and a multifunctional monomer (component c) with trifunctionality or above is preferably 0.01% to 5% by weight, more preferably 0.1% to 3.5% by weight, further preferably 0.2% to 3% by weight, particularly preferably 0.3% to 2% by weight, and most preferably 0.4% to 1.5% by weight.

[0067] Without impairing the effects of the invention, the monomer composition comprising (meth)acrylate (component a), a monomer containing a polar group (component b), and a polyfunctional monomer with trifunctionality or higher (component c) may contain any other suitable monomers. Such other monomers may be only one type or may be two or more types.

[0068] From the perspective of further demonstrating the effects of the present invention, the proportion of other monomers in the monomer composition comprising (meth)acrylate (component a), a monomer containing a polar group (component b), and a polyfunctional monomer with trifunctionality or above (component c) is preferably 0% to 10% by weight, more preferably 0% to 5% by weight, further preferably 0% to 1% by weight, particularly preferably 0% to 0.1% by weight, and most preferably 0% to 0.05% by weight.

[0069] Acrylic polymer emulsion (A) is obtained by emulsion polymerization of a monomer composition containing alkyl (meth)acrylate (component a), a monomer containing a polar group (component b), and a polyfunctional monomer with trifunctionality or higher (component c) in the presence of a reactive emulsifier (component d).

[0070] As a reactive emulsifier (component d), any reactive emulsifier is acceptable, and any suitable reactive emulsifier may be used without impairing the effects of the present invention. The reactive emulsifier (component d) may be only one type or may consist of two or more types. Here, a reactive emulsifier refers to an emulsifier having a reactive group capable of polymerizing with the monomers in the monomer composition. Examples of such reactive groups include, for instance, alkenyl groups such as vinyl, allyl, and 1-propenyl, and (meth)acryloyl groups.

[0071] In embodiments of the present invention, by employing a reactive emulsifier (component d) as the emulsifier, for example, contamination of the adhered material by the obtained acrylic adhesive can be effectively suppressed. When a non-reactive emulsifier is used as the emulsifier, the non-reactive emulsifier tends to become free in the obtained acrylic adhesive, and therefore may transfer to the adhered material, thus becoming a cause of contamination.

[0072] Examples of reactive emulsifiers (component d) include, for example, anionic reactive emulsifiers and nonionic reactive emulsifiers.

[0073] Examples of anionic reactive emulsifiers include: polyoxyethylene alkyl ether sulfates (such as the "AQUALON KH-05" series, "AQUALON KH-10" series, and "AQUALON KH-20" series manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd.; the "ADEKA REASOAP SR-10N" series and "ADEKA REASOAP SR-20N" series manufactured by ADEKA Co., Ltd.; and the "LATEMUL PD-104" series manufactured by Kao Corporation; etc.); polyoxyethylene styrene phenyl ether sulfates (such as the "AQUALON AR-10" series and "AQUALON AR-20" series manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd.; etc.); and sulfosuccinates (such as the "LATEMUL S-120" series and "LATEMUL S-120" series manufactured by Kao Corporation). S-120A series, LATEMULS-180P series, LATEMUL S-180A series; ELEMINOL JS-2 series manufactured by Sanyo Chemical Co., Ltd.; etc.; polyoxyethylene nonylpropene phenyl ether sulfates (AQUALON HS-10 series, AQUALON HS-20 series, AQUALON HS-30 series, AQUALON BC-10 series, AQUALONBC-20 series manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd.; ADEKA REASOAP SDX-222 series, ADEKA REASOAP SDX-223 series, ADEKA REASOAP SDX-232 series, ADEKA REASOAP SDX-233 series, ADEKA REASOAP SDX-233 series, ADEKA REASOAP SDX-233 series, ADEKA REASOAP SDX-222 series, ADEKA REASOAP SDX-2 ... SDX-259 series, ADEKA REASOAP SE-10N series, ADEKA REASOAP SE-20N series, etc.; (meth)acrylate sulfates (Antox MS-60 series and Antox MS-2N series manufactured by Nippon Emulsifier Co., Ltd.; ELEMINOL RS-30 series manufactured by Sanyo Chemical Co., Ltd., etc.); phosphate esters (H-3330PL series manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd.; ADEKA REASOAP PP-70 series manufactured by ADEKA Co., Ltd., etc.).

[0074] Examples of nonionic reactive emulsifiers include: polyoxyethylene alkyl ethers (such as the "ADEKA REASOAP ER-10" series, "ADEKA REASOAP ER-20" series, "ADEKA REASOAP ER-30" series, and "ADEKA REASOAP ER-40" series manufactured by ADEKA Corporation; the "LATEMUL PD-420" series, "LATEMUL PD-430" series, and "LATEMUL PD-450" series manufactured by Kao Corporation; etc.); polyoxyethylene styrene phenyl ethers (such as the "AQUALON AN-10" series and "AQUALON AN-20" series manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd.); and polyoxyethylene alkyl phenyl ethers or alkyl phenyl esters (such as the "AQUALON" series manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd.). RN-10 series, AQUALON RN-20 series, AQUALON RN-30 series, AQUALON RN-50 series; ADEKA REASOAP NE-10 series, ADEKA REASOAP NE-20 series, ADEKA REASOAP NE-30 series, ADEKA REASOAP NE-40 series manufactured by ADEKA Co., Ltd.; etc.; (meth)acrylate sulfate series (RMA-564 series, RMA-568 series, RMA-1114 series manufactured by Nippon Emulsifier Co., Ltd., etc.).

[0075] As a reactive emulsifier (component d), from the perspective of further demonstrating the effects of the present invention, anionic reactive emulsifiers can preferably be listed.

[0076] The amount of reactive emulsifier (component d) used relative to 100 parts by weight of the monomer composition comprising alkyl (meth)acrylate (component a), a monomer containing a polar group (component b), and a polyfunctional monomer with trifunctionality or higher (component c) is preferably 0.5 parts by weight to 10 parts by weight, more preferably 1.0 parts by weight to 8 parts by weight, even more preferably 1.2 parts by weight to 6 parts by weight, and particularly preferably 1.5 parts by weight to 5 parts by weight. If the amount of reactive emulsifier (component d) used deviates from the above range and is too small, the emulsion polymerization may become unstable. If the amount of reactive emulsifier (component d) used deviates from the above range and is too large, there will be more unreacted reactive emulsifier (d), which may transfer to the adherend and become a cause of contamination.

[0077] Without impairing the effects of the present invention, the reactive emulsifier (component d) may be used in combination with non-reactive anionic emulsifiers and non-reactive nonionic emulsifiers as needed.

[0078] Examples of non-reactive anionic emulsifiers include alkyl sulfates, alkylbenzene sulfonates, alkyl sulfosuccinates, alkyl diphenyl ether disulfonates, polyoxyethylene alkyl sulfates, and polyoxyethylene alkyl phosphates. Examples of non-reactive nonionic emulsifiers include polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, ethylene oxide-propylene oxide block polymers, sorbitan fatty acid esters, and polyoxyethylene fatty acid esters.

[0079] In emulsion polymerization, a polymerization initiator is preferred. The polymerization initiator can be one or more. Examples of polymerization initiators include: persulfates such as potassium persulfate, sodium persulfate, and ammonium persulfate; hydrogen peroxide; 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-amidinylpropane) dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis{2-[N-(2-carboxyethyl)amidinyl]propane} n-hydrate, and 2,2'-azobis(N,N '-Dimethyl isobutylamidine), 2,2'-azobis(2,4-dimethylpentanonitrile), 2,2'-azobis(2-methylbutanonitrile), ammonium (amine) salts of 4,4'-azobis-4-cyanopentanoic acid, 2,2'-azobis(2-methylamidooxime) dihydrochloride, 2,2'-azobis(2-methylbutanonitrileoxime) dihydrochloride tetrahydrate, 2,2'-azobis{2-methyl-N-[1,1] Azo initiators such as bis(hydroxymethyl)-2-hydroxyethyl]-propionamide, 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)-propionamide]; alkyl peroxides, tert-butyl hydroperoxide, cumene hydroperoxide, terpene hydroperoxide, lauroyl peroxide, 3,5,5-trimethylhexanoyl peroxide, octanoyl peroxide, tert-butyl cumene peroxide, benzoyl peroxide, dichlorobenzoyl peroxide, dicumene peroxide, ditert-butyl peroxide Organic peroxides such as 1,1-bis(tert-butylperoxide)-3,3,5-trimethylcyclohexane, 3,3,5-trimethylcyclohexanone peroxide, methylcyclohexanone peroxide, diisobutyl peroxide, di(2-ethylhexyl) peroxide, and tert-butyl peroxide; redox polymerization initiators (e.g., combinations of hydrogen peroxide and ascorbic acid, combinations of hydrogen peroxide and iron(II) salts, and combinations of persulfates and sodium bisulfite); etc.

[0080] The amount of polymerization initiator used relative to 100 parts by weight of the monomer composition comprising (meth)acrylate (component a), a monomer containing a polar group (component b), and a polyfunctional monomer with trifunctionality or higher (component c) is preferably 0.001 parts by weight to 5 parts by weight, more preferably 0.01 parts by weight to 4 parts by weight, further preferably 0.03 parts by weight to 3 parts by weight, and particularly preferably 0.05 parts by weight to 2 parts by weight.

[0081] The amount of water used in emulsion polymerization can be any suitable amount without impairing the effects of the present invention. As such an amount of water, relative to 100 parts by weight of the monomer composition comprising (meth)acrylate (component a), a monomer containing a polar group (component b), and a polyfunctional monomer with trifunctionality or higher (component c), is preferably 25 to 900 parts by weight, more preferably 30 to 600 parts by weight, further preferably 35 to 500 parts by weight, particularly preferably 40 to 450 parts by weight, and most preferably 43 to 400 parts by weight.

[0082] As a method for emulsion polymerization, any suitable method may be employed without impairing the effects of the present invention. For example, such a method may be described as follows: A portion of water and a polymerization initiator are added to a reaction vessel; a monomer composition comprising alkyl (meth)acrylate (component a), a monomer containing a polar group (component b), and a multifunctional monomer with trifunctionality or higher (component c), a reactive emulsifier (d), and the remaining water are separately added to the vessel; the mixture is stirred to prepare a monomer emulsion; this monomer emulsion is then added to the aforementioned reaction vessel and heated to carry out polymerization.

[0083] As the polymerization temperature for emulsion polymerization, any suitable polymerization temperature can be used without impairing the effects of the present invention. For example, such a polymerization temperature is 50°C to 90°C.

[0084] As for the polymerization time of emulsion polymerization, any suitable polymerization time can be used without impairing the effects of the present invention. For example, such a polymerization time is 0.5 hours to 10 hours.

[0085] During emulsion polymerization, any suitable additives may be added in any appropriate amount as needed, without impairing the effects of the present invention. Examples of such additives include, for instance, tackifiers, plasticizers, preservatives / mildew inhibitors, rust inhibitors, freeze-thaw stabilizers, high-boiling-point solvents, pigments, colorants, fillers, metal powders, defoamers, thickeners, adhesion control agents, and chain transfer agents.

[0086] After emulsion polymerization, the pH can be adjusted using an alkaline compound (e.g., ammonia).

[0087] Thus, an acrylic polymer emulsion (A) containing an acrylic polymer as a solid component can be obtained, which is obtained by emulsion polymerization of a monomer composition containing an alkyl (meth)acrylate (component a), a monomer containing a polar group (component b), and a polyfunctional monomer with three or more functions (component c) in the presence of a reactive emulsifier (component d).

[0088] In one embodiment of the present invention, the crosslinking agent (B) is an oil-soluble crosslinking agent.

[0089] Oil-soluble crosslinking agents are sometimes also called water-insoluble crosslinking agents, non-hydrophilic crosslinking agents, or hydrophobic crosslinking agents. There can be only one type of oil-soluble crosslinking agent or two or more types.

[0090] Examples of oil-soluble crosslinking agents include: N,N,N',N'-tetraglycidylm-phenylenediamine, 1,3-bis(N,N-glycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, and other oil-soluble epoxy crosslinking agents; hexamethylene diisocyanate and other oil-soluble isocyanate crosslinking agents; and oil-soluble carbodiimide crosslinking agents. Among these, oil-soluble epoxy crosslinking agents are preferred from the perspective of further demonstrating the effects of the present invention.

[0091] As an oil-soluble epoxy crosslinking agent, specifically, for example, the following products manufactured by Nagase ChemteX Co., Ltd. can be used: "DENACOL EX-321", "DENACOL EX-321L", "DENACOL EX-622", "DENACOL EX-201", "DENACOL EX-201-IM", "DENACOL EX-211", "DENACOL EX-212", "DENACOL EX-212L", "DENACOL EX-252", "DENACOL EX-931", "DENACOL EX-991L", "DENACOL EX-121", "DENACOL EX-141", "DENACOL EX-142-IM", etc. EX-146", trade name "DENACOL EX-146P", trade name "DENACOL EX-192", trade name "DENACOL EX-731"; trade names "TETRAD-C" and "TETRAD-X" manufactured by Mitsubishi Gas Chemical Co., Ltd.

[0092] From the perspective of further demonstrating the effects of the present invention, the crosslinking agent (B) in the acrylic adhesive composition of the embodiments of the present invention is preferably 0.01 parts by weight to 20 parts by weight relative to 100 parts by weight of acrylic polymer (solid component), more preferably 0.05 parts by weight to 10 parts by weight, even more preferably 0.1 parts by weight to 5 parts by weight, and even more preferably 0.2 parts by weight to 4 parts by weight.

[0093] Without impairing the effects of the invention, the acrylic adhesive composition of the embodiments of the invention may contain any suitable additives in any appropriate amount as desired. Examples of such additives include, for instance, tackifiers, plasticizers, preservatives / mildew inhibitors, rust inhibitors, freeze-thaw stabilizers, high-boiling-point solvents, pigments, colorants, fillers, metal powders, defoamers, thickeners, adhesion control agents, and chain transfer agents.

[0094] Thus, the acrylic adhesive composition of the embodiments of the present invention can be obtained.

[0095] Acrylic Adhesives

[0096] The acrylic adhesive of the present invention is formed from the acrylic adhesive composition of the present invention.

[0097] The acrylic adhesive of the embodiments of the present invention can be an adhesive of any shape. Typically, the acrylic adhesive of the embodiments of the present invention is a sheet-like acrylic adhesive. As a sheet-like acrylic adhesive, it is typically an adhesive that is identified as one of the constituent components, such as an acrylic adhesive layer.

[0098] The acrylic adhesive of the embodiments of the present invention can be defined as a substance formed from an acrylic adhesive composition. This is because, in the case of acrylic adhesives, acrylic adhesive compositions become acrylic adhesives by inducing crosslinking reactions such as heating. Therefore, there are situations where it is impossible and completely impractical to directly determine the acrylic adhesive by its structure ("impossible / impractical situation"). Therefore, by defining "a substance formed from an acrylic adhesive composition", the acrylic adhesive is properly defined as a "substance".

[0099] As an embodiment of the present invention, the method for forming an acrylic adhesive can employ any suitable method without impairing the effects of the present invention. For example, a method for forming such an acrylic adhesive can be described as follows: coating an acrylic adhesive composition onto any suitable substrate, and heating / drying as needed, thereby forming an acrylic adhesive in sheet form on the substrate. As a means of coating, any suitable means can be employed without impairing the effects of the present invention. Examples of such coating means include, for example, gravure roller coating machines, reverse roller coating machines, roller coating machines, dip roller coating machines, bar coating machines, doctor blade coating machines, air knife coating machines, spray coating machines, comma coating machines, direct coating machines, and roller brush coating machines. Without impairing the effects of the present invention, any suitable means can be employed for heating / drying the acrylic adhesive composition. Examples of such heating / drying means include, for example, heating to approximately 60°C to 180°C. In addition, depending on the needs, curing can also be promoted by ultraviolet irradiation, laser irradiation, alpha irradiation, beta irradiation, gamma irradiation, X-ray irradiation, electron beam irradiation, etc.

[0100] ≪Surface Protective Film≫

[0101] The surface protective film of the embodiments of the present invention has an adhesive layer composed of an acrylic adhesive of the embodiments of the present invention.

[0102] The surface protective film of embodiments of the present invention typically comprises an adhesive layer and a substrate layer made of an acrylic adhesive of embodiments of the present invention. In addition to the adhesive layer and substrate layer made of an acrylic adhesive of embodiments of the present invention, the surface protective film of embodiments of the present invention may have any suitable other layers without impairing the effects of the present invention. The surface protective film of embodiments of the present invention typically comprises an adhesive layer and a substrate layer made of an acrylic adhesive of embodiments of the present invention.

[0103] The substrate layer can be one layer or two or more layers. From the perspective of further demonstrating the effects of the present invention, the substrate layer is preferably one layer.

[0104] The thickness of the substrate layer is preferably 1 μm to 500 μm, more preferably 5 μm to 300 μm, even more preferably 10 μm to 100 μm, particularly preferably 15 μm to 80 μm, and most preferably 20 μm to 60 μm. If the thickness of the substrate layer is within the above range, the effects of the present invention will be further demonstrated.

[0105] As the material for the substrate layer, any suitable material may be used without impairing the effects of the present invention. Resin materials are representative examples of such substrate layer materials.

[0106] Resin materials used as the substrate layer include, for example, acrylic resins such as polyimide (PI), polyetheretherketone (PEEK), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), and polymethyl methacrylate (PMMA), as well as polycarbonate, cellulose triacetate (TAC), polysulfone, polyarylate, polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, ethylene-vinyl acetate copolymer (EVA), polyamide (nylon), fully aromatic polyamide (aramid), polyvinyl chloride (PVC), polyvinyl acetate, polyphenylene sulfide (PPS), fluorinated resins, and cyclic olefin polymers.

[0107] The adhesive layer can be one layer or two or more layers. From the perspective of further demonstrating the effects of the present invention, the adhesive layer is preferably one layer.

[0108] The thickness of the adhesive layer is preferably 1 μm to 250 μm, more preferably 1 μm to 150 μm, even more preferably 2 μm to 100 μm, even more preferably 2 μm to 80 μm, even more preferably 2 μm to 50 μm, particularly preferably 3 μm to 40 μm, and most preferably 3 μm to 30 μm. If the thickness of the adhesive layer is within the above range, the effects of the present invention will be further demonstrated.

[0109] In embodiments of the present invention, the surface protective film may be equipped with any suitable release liner on the surface of the adhesive layer opposite to the substrate layer for protection before use, etc.

[0110] Examples of release liner materials include: release liner materials whose surface is treated with silicone, such as paper or plastic film; and release liner materials whose surface is laminated with polyolefin resin, such as paper or plastic film. Examples of plastic films used as release liner materials include: polyethylene film, polypropylene film, polybutene film, polybutadiene film, polymethylpentene film, polyvinyl chloride film, vinyl chloride copolymer film, polyethylene terephthalate film, polybutylene terephthalate film, polyurethane film, and ethylene-vinyl acetate copolymer film.

[0111] The thickness of the release liner can be any suitable thickness without impairing the effects of the present invention. Preferably, it is 3 μm to 200 μm, more preferably 10 μm to 100 μm, from the perspective of further demonstrating the effects of the present invention. Conventionally known release agents (e.g., silicone-based release agents, fluorine-based release agents, long-chain alkyl-based release agents, fatty acid amide-based release agents) or silica powder can be used to perform release treatment and anti-fouling treatment on the surface of the release liner that adheres to the adhesive layer.

[0112] The thickness of the surface protective film in the embodiments of the present invention is preferably 1μm to 400μm, more preferably 2μm to 300μm, further preferably 5μm to 300μm, particularly preferably 10μm to 200μm, and most preferably 20μm to 100μm.

[0113] The surface protective film of the embodiments of the present invention can be manufactured by referring to the acrylic adhesive forming method of the embodiments of the present invention described above. For example, the following method can be used: applying an acrylic adhesive composition onto a material that serves as a substrate for the surface protective film, and heating / drying as needed, thereby forming an acrylic adhesive in sheet form on the substrate.

[0114] Regarding the surface protective film in embodiments of the present invention, the low-speed initial peel force is preferably 0.05 N / 25 mm to 0.50 N / 25 mm, more preferably 0.10 N / 25 mm to 0.45 N / 25 mm, even more preferably 0.15 N / 25 mm to 0.40 N / 25 mm, even more preferably 0.20 N / 25 mm to 0.35 N / 25 mm, even more preferably 0.25 N / 25 mm to 0.35 N / 25 mm, and particularly preferably 0.27 N / 25 mm. The initial low-speed peel force is defined as follows: N / 25mm to 0.35N / 25mm, most preferably 0.27N / 25mm to 0.31N / 25mm. This initial low-speed peel force is the initial peel force when the surface protective film is peeled from the PET substrate at a peel angle of 180 degrees and a peel speed of 0.3m / min after the adhesive layer of the surface protective film has been adhered to the PET substrate for 30 minutes at 23°C and 50%RH. If the initial low-speed peel force is within the above range, the surface protective film of the embodiment of the present invention exhibits good low-speed peelability. If the initial low-speed peel force deviates from the above range and is too small, the surface protective film may peel off from the adhered object when protection is needed. If the initial low-speed peel force deviates from the above range and is too large, the surface protective film may not be able to be peeled off from the adhered object. The specific method for measuring the initial low-speed peel force is described later.

[0115] Regarding the surface protective film in embodiments of the present invention, the high-speed initial peel force is preferably 0.05 N / 25 mm to 0.50 N / 25 mm, more preferably 0.10 N / 25 mm to 0.40 N / 25 mm, even more preferably 0.12 N / 25 mm to 0.35 N / 25 mm, even more preferably 0.15 N / 25 mm to 0.33 N / 25 mm, even more preferably 0.15 N / 25 mm to 0.30 N / 25 mm, and particularly preferably 0.1 N / 25 mm. The initial high-speed peel force is 7 N / 25 mm to 0.28 N / 25 mm, most preferably 0.19 N / 25 mm to 0.26 N / 25 mm. This initial high-speed peel force is defined as the initial peel force when the surface protective film is peeled from the PET substrate at a peel angle of 180 degrees and a peel speed of 30 m / min after the adhesive layer of the surface protective film has been adhered to the PET substrate at 23°C and 50% RH for 30 minutes. If the initial high-speed peel force is within the above range, the surface protective film of the embodiment of the present invention exhibits good high-speed peelability. If the initial high-speed peel force deviates from the above range and is too small, the surface protective film may peel off from the adhered object when protection is needed. If the initial high-speed peel force deviates from the above range and is too large, the surface protective film may not be able to be peeled off from the adhered object. The specific method for measuring the initial high-speed peel force is described later.

[0116] [Example]

[0117] The present invention will now be specifically described through examples, but the present invention is not limited to these examples in any way. It should be noted that the testing and evaluation methods in the examples are as follows. It should be noted that when a quantity is described as "parts," unless otherwise specified, it refers to "parts by weight"; when a quantity is described as "%," unless otherwise specified, it refers to "% by weight."

[0118] <Determination of the measured glass transition temperature Tg>

[0119] An acrylic adhesive layer composed of an acrylic adhesive composition was stacked to form an adhesive layer approximately 1 mm thick, and then punched into a disc shape with a diameter of 8 mm, which was used as the test sample. Dynamic viscoelasticity was measured using a viscoelastic testing machine (TA Instruments, ARES) under the following conditions. Based on the test results, the temperature corresponding to the peak temperature of the loss tangent tanδ (loss modulus G” / storage modulus G’) was determined as the measured glass transition temperature Tg (unit: °C) of the acrylic adhesive.

[0120] [Measurement conditions]

[0121] • Transformation Mode: Shearing Mode

[0122] • Measurement frequency: 1Hz

[0123] • Temperature range: -50℃ to 150℃

[0124] • Heating rate: 5°C / minute

[0125] • Shape: Parallel plate, 8mm φ

[0126] <Determination of Low-Speed ​​and High-Speed ​​Initial Peel Force>

[0127] The surface protective film was cut into dimensions of 25 mm in width and 100 mm in length. After peeling off the release liner, it was laminated onto a PET substrate (manufactured by TORAY, trade name "Lumirror", thickness = 38 μm) using a 2 kg roller to produce evaluation samples.

[0128] After the above lamination, after being placed in an environment of 23°C and 50% RH for 30 minutes, a single-sided adhesive tape (manufactured by NICHIBAN, trade name "Cellotape (registered trademark)") cut to a size of 25mm in width and 50mm in length was pressed onto the substrate side of the surface protective film of the above-mentioned evaluation sample with the end face protruding 1mm (when viewed from the adhesive layer of the surface protective film, it is placed on the PET film side opposite to the PET substrate of the above-mentioned lamination), and placed for 10 seconds.

[0129] Subsequently, in an environment of 23°C and 50%RH, using a universal tensile testing machine, at a peel speed of 0.3 m / min (low-speed initial peel force) or 30 m / min (high-speed initial peel force) and a peel angle of 180°, the above-mentioned single-sided adhesive tape with the above-mentioned 1 mm protruding end face was held and the surface protective film was peeled off from the above-mentioned laminated PET substrate. The adhesive force in the area where the value stabilized was measured and set as the initial peel force (N / 25 mm).

[0130] [Example 1]

[0131] <Preparation of Acrylic Polymer Emulsions>

[0132] A monomer emulsion was prepared by mixing water (30 parts by weight), 2-ethylhexyl acrylate (2EHA) (70 parts by weight), methyl methacrylate (MMA) (30 parts by weight), acrylic acid (AA) (3 parts by weight), trimethylolpropane triacrylate (TMPTA) (1 part by weight), and reactive anionic emulsifier (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., trade name "AQUALON KH-1025", solids concentration = 25% by weight) (3 parts by weight) in a container and then stirring it using a homogenizer.

[0133] Next, water (50 parts by weight) and polymerization initiator (ammonium persulfate (APS)) (0.1 parts by weight) were added to a reaction vessel equipped with a condenser, nitrogen inlet, thermometer, and stirrer. The monomer emulsion was added over 3 hours while stirring, and then the reaction was carried out at 75°C for 3 hours. Then, it was cooled to 30°C and ammonia water with a concentration of 10% by weight was added to adjust the pH to 8, thereby preparing an acrylic polymer emulsion (1) containing acrylic polymer (1) (concentration of acrylic polymer (1) (solid component concentration) = 55% by weight).

[0134] <Preparation of Water-Dispersible Acrylic Adhesive Compositions>

[0135] In the acrylic polymer emulsion (1) prepared above, relative to the acrylic polymer (1) (solid component): 100 parts by weight, an epoxy crosslinking agent (manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name "TETRAD-C", 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, epoxy equivalent = 110, number of functional groups = 4): 1 part by weight was added as an oil-soluble crosslinking agent. The mixture was stirred and mixed using a stirrer at 23°C, 300 rpm and for 10 minutes to prepare a water-dispersible acrylic adhesive composition (1).

[0136] <Preparation of Surface Protective Film>

[0137] Using a coating applicator manufactured by Tester Sangyo Co., Ltd., the water-dispersible acrylic adhesive composition (1) prepared above was coated onto the corona-treated surface of a PET film (manufactured by Toyobo Co., Ltd., trade name "E7415", thickness = 38 μm) to a thickness of 5 μm after drying. The film was then dried in a hot air circulating oven at 130°C for 1 minute to form an acrylic adhesive layer. After attaching the obtained acrylic adhesive layer to a release liner, it was cured (aged) at room temperature for 1 week to obtain a surface protective film (1).

[0138] The results are shown in Table 1.

[0139] [Examples 2-9]

[0140] Except for changing (meth)acrylate alkyl ester (a component) to that shown in Table 1, the same procedure as in Example 1 was performed to obtain acrylic polymer emulsions (2) to (9) containing acrylic polymers (2) to (9) (concentration of acrylic polymers (2) to (9) (solid component concentration) = 45% by weight), water-dispersible acrylic adhesive compositions (2) to (9), and surface protective films (2) to (9).

[0141] The results are shown in Table 1.

[0142] [Comparative Examples 1 and 2]

[0143] Except for changing the (meth)acrylate alkyl ester (component a) to that shown in Table 1, the same procedure as in Example 1 was performed to obtain acrylic polymer emulsions (C1) and (C2) containing acrylic polymers (C1) and (C2) (concentration of acrylic polymers (C1) and (C2) (solid component concentration) = 45% by weight), water-dispersible acrylic adhesive compositions (C1) and (C2), and surface protective films (C1) and (C2).

[0144] The results are shown in Table 1.

[0145]

[0146] Industrial availability

[0147] The acrylic adhesive compositions and acrylic adhesives of the embodiments of the present invention are suitable for use as re-peelable surface protective films for bonding to the surfaces of optical devices, electronic devices, such as displays and imaging devices, and the constituent parts of these devices. The surface protective films of the embodiments of the present invention are suitable for use as re-peelable surface protective films for bonding to the surfaces of optical devices, electronic devices, such as displays and imaging devices, and the constituent parts of these devices.

Claims

1. An acrylic adhesive composition, wherein, The acrylic adhesive composition is an acrylic adhesive composition comprising an acrylic polymer. The measured glass transition temperature (Tg) of the acrylic adhesive formed from this acrylic adhesive composition is -25℃ to 15℃.

2. The acrylic adhesive composition according to claim 1, wherein, The measured glass transition temperature Tg is -15℃ to 5℃.

3. The acrylic adhesive composition according to claim 1, wherein, The acrylic adhesive composition is a water-dispersible acrylic adhesive composition comprising acrylic polymer emulsion A and crosslinking agent B.

4. The acrylic adhesive composition according to claim 3, wherein, The acrylic polymer emulsion A is obtained by emulsion polymerization of a monomer composition comprising (meth)acrylate alkyl ester as component a, a monomer containing a polar group as component b, and a multifunctional monomer with trifunctionality or higher as component c, in the presence of a reactive emulsifier as component d.

5. The acrylic adhesive composition according to claim 4, wherein, The alkyl methacrylates used as component a are two or more components, and the difference between the maximum and minimum values ​​of the octanol / water partition coefficient LogPow shown by the alkyl methacrylates used as component a is 0.5 or more.

6. The acrylic adhesive composition according to claim 5, wherein, The difference between the maximum and minimum values ​​in the octanol / water partition coefficient LogPow is greater than 1.

0.

7. The acrylic adhesive composition according to claim 4, wherein, The alkyl methacrylate used as component a is a combination of methyl methacrylate and alkyl methacrylate having 2 to 8 carbon atoms.

8. The acrylic adhesive composition according to claim 4, wherein, The polar monomer that constitutes component b is at least one selected from the group consisting of hydroxyl-containing monomers and carboxyl-containing monomers.

9. The acrylic adhesive composition according to claim 4, wherein, The reactive emulsifier used as component d is an anionic reactive emulsifier.

10. The acrylic adhesive composition according to claim 3, wherein, The crosslinking agent B is an oil-soluble crosslinking agent.

11. The acrylic adhesive composition according to claim 10, wherein, The crosslinking agent B is an oil-soluble epoxy crosslinking agent.

12. An acrylic adhesive formed from an acrylic adhesive composition as described in any one of claims 1 to 11.

13. A surface protective film, wherein, It has an adhesive layer made of an acrylic adhesive as described in claim 12.

Citation Information

Patent Citations

  • Surface-protection sheet

    JP1986268782A

  • Peelable aqueous adhesive composition

    JP2004256789A

  • Adhesive composition, pressure sensitive adhesive double coated tape, adhesion method and portable electronic device

    JP2007051271A